2013
DOI: 10.1039/c3nr03348a
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, conductive, and SERS-active Au nanofiber films assembled on an amphiphilic peptide template

Abstract: The use of biological materials as templates for functional molecular assemblies is an active research field at the interface between chemistry, biology, and materials science. We demonstrate the formation of gold nanofiber films on β-sheet peptide domains assembled at the air/water interface. The gold deposition scheme employed a recently discovered chemical process involving spontaneous crystallization and reduction of water-soluble Au(SCN)4(1-) upon anchoring to surface-displayed amine moieties. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Beyond 1-D structures, noble metal catalysts with 2-D structures can also be obtained by employing a peptide template whose nanofibers can undergo further associations to form nanofilms. 55,56 One such example is provided by Jelinek and his co-workers, who synthesized transparent and conductive Au nanofiber films on a peptide monolayer. 56 After peptide P FK -5 ((Phe-Lys) 5 -Pro) self-assembled into a nanofilm, a TEM grid was used to load the peptide film and then floated over an aqueous solution of Au(SCN) 4 1– .…”
Section: Synthesis Of Peptide-templated Noble Metal Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond 1-D structures, noble metal catalysts with 2-D structures can also be obtained by employing a peptide template whose nanofibers can undergo further associations to form nanofilms. 55,56 One such example is provided by Jelinek and his co-workers, who synthesized transparent and conductive Au nanofiber films on a peptide monolayer. 56 After peptide P FK -5 ((Phe-Lys) 5 -Pro) self-assembled into a nanofilm, a TEM grid was used to load the peptide film and then floated over an aqueous solution of Au(SCN) 4 1– .…”
Section: Synthesis Of Peptide-templated Noble Metal Catalystsmentioning
confidence: 99%
“…55,56 One such example is provided by Jelinek and his co-workers, who synthesized transparent and conductive Au nanofiber films on a peptide monolayer. 56 After peptide P FK -5 ((Phe-Lys) 5 -Pro) self-assembled into a nanofilm, a TEM grid was used to load the peptide film and then floated over an aqueous solution of Au(SCN) 4 1– . The negatively charged Au complexes bind to the peptide film and then reduce into metallic Au.…”
Section: Synthesis Of Peptide-templated Noble Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that Au(SCN) 4 − selfassembles into conductive Au 0 nanostructures through singlestep crystallization/reduction process which do not require addition of reducing agents. [23][24][25] Here we show that a surfactant, octyl-melamine (OM), adopts elongated and aligned micro-wire morphology when isothermally compressed at the air/water interface. Furthermore, the OM assemblies constitute a template for gold deposition through electrostatic attraction between the primary amine residues of the surfactant and soluble Au(SCN) 4 − , accompanied by spontaneous crystallization and reduction of gold by the thiocyanate moieties, without addition of reducing agents.…”
mentioning
confidence: 98%
“…88 This peptide was also shown to template calcium phosphate mineralisation, making it potentially applicable in bone tissue regeneration. Vinod et al 109 recently reported the peptide P FK -5, which incorporated the cationic lysine as the charged hydrophilic residue. This peptide assembled at air-water interfaces and was able to template gold nanofibre film formation.…”
mentioning
confidence: 99%